On Rainbow Trees and Cycles - Frieze, Alan; Krivelevich, Michael (The Electronic Journal of Combinatorics, 2008)
We derive sufficient conditions for the existence of rainbow cycles of all lengths in edge colourings of complete graphs. We also consider rainbow colorings of a certain class of trees.